Magnetic Fields in Diffuse Media - Lazarian, Alexander.; Lazarian, Alexander.; de Gouveia Dal Pino, Elisabete M.; de Gouveia Dal Pino, Elisabete M.; Melioli, Claudio.; Melioli, Claudio. (Astrophysics and Space Science Library,, 2015)
This volume presents the current knowledge of magnetic fields in diffuse astrophysical media. Starting with an overview of 21st century instrumentation to observe astrophysical magnetic fields, the chapters cover observational techniques, origin of magnetic fields, magnetic turbulence, basic processes in magnetized fluids, the role of magnetic fields for cosmic rays, in the interstellar medium and for star formation. Written by a group of leading experts the book represents an excellent overview of the field. Nonspecialists will find sufficient background to enter the field and be able to appreciate the state of the art.